The discrete compactness property for anisotropic edge elements on polyhedral domains - Lombardi, Ariel Luis (2012)
We prove the discrete compactness property of the edge elements of any order on a class of anisotropically refined meshes on polyhedral domains. The meshes, made up of tetrahedra, have been introduced in [Th. Apel and S. Nicaise, Math. Meth. Appl. Sci. 21 (1998) 519?549]. They are appropriately graded near singular corners and edges of the polyhedron.